2020
DOI: 10.1111/cns.13428
|View full text |Cite
|
Sign up to set email alerts
|

Laminin degradation by matrix metalloproteinase 9 promotes ketamine‐induced neuronal apoptosis in the early developing rat retina

Abstract: Aims During early development, laminin degradation contributes to the death of neurons. This study aims to investigate the role and regulation of laminin in ketamine‐induced apoptosis. Methods We performed terminal deoxynucleotidyl transferase biotin‐dUTP nick end labeling (TUNEL) and immunohistochemical assays to investigate the roles of the non‐integrin laminin receptor, matrix metalloproteinase 9 (MMP9) in ketamine‐induced neuronal apoptosis. In situ zymography, Western blot, and immunofluorescence were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…47 Moreover, the accumulation of microglia (1 day after ICH) happened earlier than previously reported (3-7 days after ICH). 33 In our study, iron intervention also influenced the upregulation of MMP9, which might degrade vascular laminin and collagen IV and corrode the vessel wall 48 and is associated with ICH enlargement and perihematoma edema. 49 The mechanisms of increased iron accumulation in the brain tissues of Ang II-induced hypertensive mice remain unclear.…”
Section: Con Clus Ionsupporting
confidence: 51%
“…47 Moreover, the accumulation of microglia (1 day after ICH) happened earlier than previously reported (3-7 days after ICH). 33 In our study, iron intervention also influenced the upregulation of MMP9, which might degrade vascular laminin and collagen IV and corrode the vessel wall 48 and is associated with ICH enlargement and perihematoma edema. 49 The mechanisms of increased iron accumulation in the brain tissues of Ang II-induced hypertensive mice remain unclear.…”
Section: Con Clus Ionsupporting
confidence: 51%
“…29,30 On the other hand, other BAG family members have been shown to protect cell death from ketamine-induced. 4 In our study, we found that miR-22 can directly bind to BAG5 mRNA and inhibit its translation, and that ketamine upregulates BAG5 in a concentration-dependent manner. This indicates that miR-22 mitigates ketamine-induced neurotoxicity in PC12 cells in part by downregulating BAG5.…”
Section: Discussionmentioning
confidence: 52%
“…1,2 Retinal cell survival involves redox signaling and a balance between reactive oxygen species (ROS) and antioxidant scavengers to counteract OS injury. [3][4][5] The retina is susceptible to OS due to its elevated oxygen consumption and exposure to visible light, which can potentiate cellular damage caused by ROS. 6 Elevated OS levels determine dramatic changes that lead to visual impairment.…”
Section: Introductionmentioning
confidence: 99%